Comparison of washing methods in sol-gel-based nanoencapsulation of paraffins for thermal energy storage: From synthesis to scalability - Kim, Somin; Gang, Kamchan; Jo, Byeongnam (Journal of Energy Storage, 2024)
The sol-gel method is widely utilized for encapsulating phase change materials (PCMs) in latent heat storage (LHS) systems. Enhancing the thermal performance of PCM capsules is crucial for increasing the storage density of LHS systems and enabling commercial scalability. This study explores two washing methods, filtration, and centrifugation, in sol-gel-based nanoencapsulation to assess the thermal performance and reliability of paraffin nanocapsules. Morphological and thermal characteristics of the paraffin nanocapsules were analyzed using scanning electron microscopy and differential scanning calorimetry. Spherical paraffin nanocapsules with minimal aggregation were obtained using both filtration and centrifugation methods. However, the filtration method yielded nanocapsules with a higher encapsulation ratio compared to centrifuged ones. The thermal stability of the nanocapsules was confirmed by direct heating on a hotplate at 100 °C for 1 h. Exceptional thermal reliability was demonstrated through 100 repeated heating and cooling cycles between 0 and 100 °C, with no decrease in melting enthalpy and perfectly matched melting curves in the DSC analysis. Hence, the filtration method is appropriate in the sol-gel based nanoencapsulation of PCM to increase the latent heat capacity of the PCM nanoencapsulation without loss of thermal stability and reliability. Furthermore, the scalability of the nanoencapsulation technique was evaluated by synthesizing up to 20 times the initial scale, assessing morphological features, thermal performance, and reliability.
Keywords: Filtration methods; Gel-based; Latent heat storage system; Nano-encapsulation; Performance and reliabilities; Phase Change; Sol'gel; Thermal; Thermal Performance; Thermal reliability; Filtration; Nanoencapsulation; Phase change material; Scalability; Sol-gel